Preservation of Environmental Ethics Based on Local Wisdom Through Traditional Agriculture Kampung Naga Community - Erni Mulyanie; Muhamad Fauzi Efendi (West Science Interdisciplinary Studies, 2023)
One of the indigenous peoples in Indonesia who still practices a traditional agricultural system that relies on crops to meet their daily needs is the residents of Kampung Naga Tasikmalaya. The people of Kampung Naga can take advantage of everything in their natural environment, but must still preserve and restore these natural products so that the natural conditions in Kampung Naga remain sustainable until now and until the future to ensure the lives of future generations. This study aims to examine community activities in preserving the environment and local wisdom that is still practiced by the people of Kampung Naga in agriculture. The method used in this study is a descriptive qualitative approach with data collection techniques used in the form of observation techniques, interviews, documentation techniques, and literature review. The results of the study show that the people of Kampung Naga in their daily lives hold strong local wisdom values so that they have a positive impact on environmental sustainability. The procedures for processing and breeding agricultural land in Kampung Naga are still traditional and based on tradition.